Gefitinib plus tremelimumab combination in refractory non-small cell lung cancer patients harbouring EGFR mutations: The GEFTREM phase I trial. (April 2022) - Riudavets, Mariona; Naigeon, Marie; Texier, Matthieu; Dorta, Miriam; Barlesi, Fabrice; Mazieres, Julien; Varga, Andrea; Cassard, Lydie; Boselli, Lisa; Grivel, Jonathan; NgoCamus, Maud; Lacroix, Ludovic; et al.
Highlights: GEFTREM evaluates tremelimumab plus gefitinib in refractory EGFR -mutant NSCLC Grade 3 TRAEs occurred in 81% patients, mostly diarrhoea and ALT/AST increase SD was the best overall response in 72% patients, with a median PFS of 2.2 months GEFTREM is the only study combining a first-generation EGFR-TKI with an anti-CTLA-4 Toxicity and limited efficacy prevented further evaluation of tremelimumab plus gefitinib Abstract: Introduction: A phase I open-label multicentre study was initiated to evaluate the association of tremelimumab with gefitinib in EGFR -mutant NSCLC patients who progressed after first-generation EGFR-TKI. Here we provide the efficacy data from the entire cohort. Material and methods: Patients with advanced EGFR- mutant NSCLC with progression after response to EGFR-TKI were enrolled. Study treatment was gefitinib 250 mg daily and tremelimumab at 3 dose levels: 3, 6 and 10 mg/kg IV Q4W for 6 cycles followed by Q12W until progression or unacceptable toxicity. The primary objective was safety and tolerability, and to establish a RP2D. Results: Between January 2014 and July 2015, 27 patients (21 in the escalating dose cohort and 6 in expansion cohort) received at least one dose of tremelimumab. DLTs occurred in 4 patients: 1 at 3 mg/kg (one grade 3 diarrhoea), 1 at 6 mg/kg (one grade 3 diarrhoea) and 2 at 10 mg/kg (one grade 3 diarrhoea and one grade 3 AST/ALT increase) of tremelimumab. Grade 3 TRAE occurred in 22 patients (81%), most frequently diarrhoea (30%) and ALT/AST increase (15%). Stable disease was the best overall response in 72% patients, with median PFS of 2.2 months (95% CI, 1.8–4.2). All patients discontinued treatment, most frequently due to disease progression (63% of patients). Conclusion: The recommended dose of tremelimumab in combination with gefitinib in EGFR -mutant NSCLC patients was 3 mg/kg. The gastrointestinal toxicity and the limited efficacy data prevented further evaluation of this combination. (GEFTREM; clinical trial number NCT02040064)